Rule, what rule? : Argentina and its monetary policy rule - Neder, Ángel Enrique (2018)
The choice of a control variable for monetary policy characterizes the welfare (loss) function that a central bank will want to maximize (minimize). Even, it gives rise to the proposal of following a rule versus applying -in a discretionally way- a monetary policy. When discussing the application of a rule, its manifestation may not be completely explicit. In this paper we try to establish a monetary policy rule for Argentina, working with an extended Taylor Rule, contemplating the influence of the exchange rate and the fiscal deficit during the last thirteen years.